2009
DOI: 10.1002/polb.21730
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of multicomponent polymer trilayers with resonant soft X‐ray reflectivity

Abstract: Resonant soft X‐ray reflectivity (RSoXR) has been used to quantify the layer thicknesses and the interfacial widths of a single, complex thin film with three polymeric layers supported on an inorganic substrate. By adjusting the photon energy, the sensitivity to particular interfaces within the trilayer can be selectively enhanced. The results significantly improve and broaden the capabilities of RSoXR, which has previously only been demonstrated and used for bilayers on silicon substrates. The capability of R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…This is in agreement with prior fits using a simplified bilayer model. 24 Furthermore, the data at energies below 283.9 eV contains information about the interfacial widths or roughnesses of the PEDOT:PSS/ITO and the ITO/glass interfaces. For the 270 eV data, a complete fit over the full q range with all adjustable parameters is not converging, due possibly to some background and normalization issues in that data.…”
Section: Cpe/meh-ppv Bilayersmentioning
confidence: 99%
See 2 more Smart Citations
“…This is in agreement with prior fits using a simplified bilayer model. 24 Furthermore, the data at energies below 283.9 eV contains information about the interfacial widths or roughnesses of the PEDOT:PSS/ITO and the ITO/glass interfaces. For the 270 eV data, a complete fit over the full q range with all adjustable parameters is not converging, due possibly to some background and normalization issues in that data.…”
Section: Cpe/meh-ppv Bilayersmentioning
confidence: 99%
“…A simplified and incomplete analysis of this multilayer has been reported previously. 24 It is demonstrated that the interfacial widths between the active CPE/MEH-PPV layers in the actual device are slightly larger than in the model bilayers. They are sufficiently similar to each other, though, that the more simple bilayer structures can be used as a proxy to investigate the influence of fabrication methods and procedures on the interfacial width between active layers.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Conventional X-ray reflectivity has little sensitivity to investigate this material pair as shown in Fig. 2 [46]. In contrast, R-SoXR has excellent contrast and was used to show with high precision that the differential casting of CPEs on top of MEH-PPV yields sharp and smooth interfaces with an RMS width of only 0.8 nm [13].…”
Section: Characterization Of Bilayer and Multilayers Used In Organic mentioning
confidence: 99%
“…Soft X-ray resonant reflectivity/scattering studies are finding application in soft mater polymer films [37][38][39][40][41][42][43][44][45][46], and biological samples [47]. However the utility of soft Xray resonant for studies of atomic composition at buried interface, depth profiling of variation in atomic density, native oxide and films of nearly equal electron density studies of hard condensed matter thin films/multilayers is not significantly exploited.…”
Section: Introductionmentioning
confidence: 99%